Piano Rhythmic Exercise for Preschool Education Major Teaching at Taiyuan Teacher College - Wen Jing; Pramote Danprdit (Journal of Green Learning, 2022)
The purpose of this paper is to create piano rhythm exercises and to study the evaluation results after use. The researcher designed the research as experimental research, consisting of a single set of experiments verifying the consistency and effectiveness of the tool. The researchers created and developed piano rhythm exercises with three experts in an experiment with 22 piano beginners majoring in preschool education. The study was conducted from September to December 2021 at Taiyuan Teacher College. Results showed that the creation of the piano rhythm exercises course is effective; it consists of 9 weeks of teaching, 3 weeks of examination, and concludes with 12 weeks of using 9 etudes and 6 children's songs. In the evaluation performance results, the average scores of the 3 tests were 27.45, 28.77, 33.16 respectively and the percentage scores were 68.64, 71.93, 82.9 respectively. However, after the test, the students who participated in the activity felt fun, were willing to practice, and, of course, had higher skills. All students request a practice file for further use.